Therapeutic Prospects of Mesenchymal Stem Cell and Their Derived Exosomes in the Regulation of the Gut Microbiota in Inflammatory Bowel Disease - Yaru Qiao; Xiaohua Tang; Ziyue Liu; Dickson Kofi Wiredu Ocansey; Mengjiao Zhou; Anquan Shang; Fei Mao (MDPI AG, 2024)
Mesenchymal stem cells (MSCs) have shown great potential in the treatment of several inflammatory diseases due to their immunomodulatory ability, which is mediated by exosomes secreted by MSCs (MSC-Exs). The incidence of inflammatory bowel disease (IBD) is increasing globally, but there is currently no long-term effective treatment. As an emerging therapy, MSC-Exs have proven to be effective in alleviating IBD experimentally, and the specific mechanism continues to be explored. The gut microbiota plays an important role in the occurrence and development of IBD, and MSCs and MSC-Exs can effectively regulate gut microbiota in animal models of IBD, but the mechanism involved and whether the outcome can relieve the characteristic dysbiosis necessary to alleviate IBD still needs to be studied. This review provides current evidence on the effective modulation of the gut microbiota by MSC-Exs, offering a basis for further research on the pathogenic mechanism of IBD and MSC-Ex treatments through the improvement of gut microbiota.